Small hepatocellular carcinoma: which criteria for liver transplantation? - Levi Sandri, Giovanni Battista (Translational Cancer Research, 2017)
Hepatocellular carcinoma (HCC) is the most common hepatic tumor and the best options for treatments are liver resection and liver transplantation. Many new locoregional treatments are available for HCC. Of them, radioembolization is the most discussed innovative one (1-3). Liver transplantation has the advantage to cure both tumor as well as the underlying cirrhosis and is the ideal treatment for HCC in cirrhotic liver.